Aplikasi Katalis Heterogen (H-Zeolit) pada Prototype Fluidized Bed Reactor Secara Batch untuk Produksi Biodiesel dari Fatty Acid Methyl Ester - Furia Andani; Pardi -; Eka Kurniasih (Politeknik Negeri Lhokseumawe, 2017)
Biodiesel is an alternative energy diesel / solar is usually produced through esterification and transesterification. Usually biodiesel produced using a homogeneous catalyst (alkaline/acid). There are weaknesses in homogeneous alkaline catalysts (KOH and NaOH), the soap will appear at the end of the biodiesel production process and very difficult when the separation (separation). Heterogeneous catalyst is a homogeneous catalyst solution to replace due to different phase reactants, a heterogeneous catalyst is zeolite, zeolite catalyst are very easily separated and do not form soap at the end of the biodiesel production process. In previous research, biodiesel is produced using a laboratory scale reactor neck flask 3. Therefore, in this research developed the biodiesel production process of fatty acid methyl ester (FAME) using zeolite catalyst H+ in the fluidized bed reactor prototype. Zeolite catalyst performance can be enlarged with the filling material into the zeolite KI. Prototype fluidized bed reactor is operated at the speed of the flow rate of 5 liter / min and the fluidization in the reactor with the minimum fluidization velocity 1.24 cm/s, the weight ratio of zeolite catalyst 2.5% (w/w), mole ratio of methanol : FAME conversion of methyl ester obtained in the 80 minute, is 69.58%